Inteksi famili x lokasi pada uji keturunan generasi kedua acacia mangium di sumatera dan kalimantan - Setyaji, Teguh (Jurnal Pemuliaan Tanaman Hutan, 2013)
The study was conducted to investigate the existence of Â family Ã site Â interactions observed in Â second generation Â open-pollinated progeny test Â ofÂ  Acacia mangium in two locations: Lipatkain, Riau (Sumatra) andÂ  Kenangan, East Kalimantan.Â  The progeny tests were Â establishedÂ Â  usingÂ  51-55 familiesÂ  originated Â from Oriomo River Papua New Guinea Â provenance. There were 31common families tested at the both sites. Growth on both sites was significantly different between families. The averageÂ  height Â and diameter was 15,9 m andÂ  13,3 cm Â respectively at Â Kenangan, and Â 17,0 m and Â 16,6 cm Â respectively at Â Lipatkain. Family Ã site interactionsÂ  were Â highly significant for height and diameter. The ratio of variance component of interaction to the family variance component (s2fl / s2f ) for Â diameter (1,6) and height (1,2) were largerr thanÂ  Shelbourneâs Â critical value (0,5), Â Â Â indicating the lowÂ  Â genotypic stability at family level for the both traits Â where theÂ  diameter was Â more sensitive than height to changing Â site conditions. Genetic correlations between the same trait at different sites were low: Â 0.45 for height Â and 0.38 for diameter. The greatest genetic gain and relative efficiency of family selection were generally expected from selecting and planting families in the same site.